Life in citations biblical narratives and contemporary Hebrew culture - Tsoffar, Ruth (Routledge studies in comparative literature, 2020)
"In her latest book, Life in Citiations: Biblical Narratives and Contemporary Hebrew Culture, Ruth Tsoffar studies several key biblical narratives that figure prominently in Israeli culture. Life in Citations provides a close reading of these narratives, along with works by contemporary Hebrew Israeli artists that respond to them. Together they read as a modern commentary on life with text, or even life under the rule of its verses, to answer questions like How can we explain the fascination and intense identification of Israelis with the Bible? What does it mean to live in such close proximity with the Bible, and What kind of story can such a life tell?"--